Sensory Characteristics and Nutritional Value of Taiyaki with the Addition of Spirulina sp. Powder - Eka Nurinsani, Anisa; Sulmartiwi, Laksmi; Andriyono, Sapto (Journal of Marine and Coastal Science, 2023)
Spirulina is known as a superfood because it is rich in nutrients, both macro and micro. Spirulina has high levels of protein, potassium and polyunsaturated fatty acids (PUFAs) which contain essential amino acids, phycocyanins, essential vitamins and antioxidants. The high nutritional content of Spirulina causes the higher utilization of Spirulina in food products. Taiyaki is a food product originating from Japan and also popular in Korea (bungeo-ppang). The research design consisted of four treatments and five replications. The treatment of adding Spirulina sp powder into the taiyaki filling as much as 1, 2, and 3% of the weight of the filling. The results of the Kruskal Wallis test showed that the addition of Spirulina sp powder had no effect on the parameters of appearance, aroma and texture, on the contrary it had a significant effect on the parameters of taste. The results of the Mann-Whitney follow-up test, the level of preference for taste parameters was not significantly different (p> 0.05) between P0 (without the addition of Spirulina sp powder) and the treatment with the addition of Spirulina sp powder 1% (P1), 2% (P2), and 3% (P3) of the filling weight. The addition of Spirulina sp. in taiyaki products can increase the nutritional value of taiyaki, especially the protein (3.61%) and fat (2.63%) components.